The Strategic Role of Human Resource Management in Achieving Organisational Goals - Indra Rustiawan; Silvy Sondari Gadzali; Yayat Suharyat; Udi Iswadi; Abu Muna Almaududi Ausat (Innovative: Journal Of Social Science Research, 2023)
This topic is related to the era of increasingly fierce business competition. In this competition, organisations are required to be able to adapt quickly and have an advantage that distinguishes them from their competitors. So, research on the strategic role of HRM in achieving organisational goals is very important to do, and is expected to provide a better understanding for organisations about the importance of HRM as a key factor in achieving organisational goals. This research is qualitative in nature. The methodology used to collect data included attentive listening and careful documentation of relevant information, which was then subjected to analytical procedures such as data reduction, data display, and conclusion drawing. The study arrived at the conclusion that, HRM has an important strategic role in achieving organisational goals. In an increasingly complex business environment, HRM can help organisations face challenges and intensified competition, build a positive image, increase customer satisfaction, and improve the efficiency and effectiveness of human resource management.